TOLERANCE AND ITS ROLE IN ENSURING FAMILY WELFARE IN THE TEACHINGS OF SUFISM (Scientific journal of the Fergana State University, 2024)
In this article, the concept of tolerance in the teachings of Sufism means being patient and resistant to the behavior, lifestyle, opinions, speech, feelings, beliefs, and actions of others and its role in ensuring the well-being of the family.